The Role of Financial Behavior in Mediating Financial Literacy, Financial Attitudes, Business Performance and Business Sustainability in MSMEs in Jayapura City - Pascalina Van Sweet Sesa; Klara Wonar; Theo Allolayuk (AIBPM Publisher, 2024)
Examining the mediating role of financial behavior on the relationships between financial literacy, financial attitudes, business performance, and the sustainability of MSMEs in Jayapura City is the aim of this study. It is anticipated that the analysis will serve as a helpful guide for the next studies. This study is quantitative in nature and tests hypotheses using a descriptive methodology. The way that data is gathered is through distributing questionnaires. One tool for data analysis methods is WarpPLS analysis. The findings showed that as a mediating variable between financial literacy and company performance, financial management behavior has a big impact on the sustainability of businesses. This indicates that MSME owners in Jayapura City are aware that taking financial literacy-related actions will assist the long-term viability of their company. Nevertheless, financial management behavior characteristics are unable to moderate the relationship between financial attitudes toward company sustainability among MSME actors in Jayapura City. It is anticipated that similar future studies can be conducted with a moderation or intervention approach and apply wider data, for example, in provincial-level areas, to create conclusions that are more applicable to the expansion of MSMEs in other locations.